Dynamics in the history of religions between Asia and Europe: encounters, notions, and comparative perspectives - Krech, Volkhard; Steinicke, Marion (Dynamics in the history of religions, 2012)
Preliminary Material /Chiara Giorgetti -- Introduction /Marion Steinicke -- Dynamics in the History of Religions – Preliminary Considerations on Aspects of a Research Programme /Volkhard Krech -- The Formation of the Major Religious Traditions Through Inter-Religious Contact Dynamic Approaches to Antique Religions in the East and West. Beyond Centres and Boundaries /Peter Wick -- Religious Formations and Intercultural Contacts in Early China /Victor H. Mair -- A comment on Victor H. Mair’s “Religious Formations and Intercultural Contacts in Early China” /Heiner Roetz -- Kings, Ascetics, and Brahmins: /Patrick Olivelle -- Did the Buddha Emerge from a Brahmanic Environment? The Early Buddhist Evaluation of “Noble Brahmins” and the “Ideological System” of Brahmanism /Jens Schlieter -- The History of Religions as a Subversive Discipline: /Guy G. Stroumsa -- Whirlpool Effects and Religious Studies. A Response to Guy G. Stroumsa /Sarah Stroumsa -- Contacts Between the Major Religious Traditions During Their Expansion Contacts between the Major Religious Traditions during their Expansion. An Introduction /Nikolas Jaspert -- The Jewish Reaction to the Islamic Conquests /Michael Lecker -- Christian Reactions to Muslim Conquests (1st–3rd Centuries AH; 7th–9th Centuries AD) /Tolan John -- Intercultural Encounter in the History of Political Thought Christian Wolff, Chŏng Yag-yong and Matteo Ricci /Eun-jeung Lee -- Jesuit Mission in Korean Studies. A Response to Eun-jeung Lee /Michael Lackner -- The Expansion of Buddhism in South and Southeast Asia /Stephen C. Berkwitz -- Response: /Sven Bretfeld -- The Notion of Religion and Religious Semantics in a Cross-Cultural Perspective Religion to the Power of Three /Lucian Hölscher -- World Religions and the Theory of the Axial Age /Jan Assmann -- Chinese History and Writing about ‘Religion(s)’: /Robert Ford Campany -- A Response to Robert Ford Campany’s “Chinese History and its Implications for Writing ‘Religion(s)’” /Russell T. McCutcheon -- Terminology and Religious Identity: /Tim H. Barrett and Francesca Tarocco -- Canon and Identity in Indian Esoteric Buddhism as the Confluence of Cultures /Ronald M. Davidson -- The Christian Canon in a Comparative Perspective. A Response to Ronald M. Davidson /Markus Zehnder -- The Christian-Muslim Encounters on the Question of Jihad /Muhammad Aslam Syed -- Religion in the Age of Globalization Shrinking World, Expanding Religion? The Dynamics of Religious Interaction in the Times of Colonialism and Globalization /Marion Eggert -- On Resilience and Defiance of the Īlamtamil Resistance Movement in a Transnational Diaspora /Peter Schalk -- Observing Religion in a Globalized World: /Peter Beyer -- Religion in a Globalised World: /Ian Reader -- Religion, Secularization, and Sacralization /José Casanova -- Multi-media Performance Reflecting Religious Dynamics. /Heinz Georg Held -- Bibliography /Volkhard Krech and Marion Steinicke -- Index /Volkhard Krech and Marion Steinicke.
Includes bibliographical references and index
Keywords: Konferenzschrift -- 2008 -- Bochum; Geschichte; Kulturkontakt; Weltreligion; Asien; Europa